A kind of hot and cold shock resistant epoxy potting glue and preparation method thereof
By using modified epoxy resin and composite filler in the potting glue, the problem of mechanical performance of the potting glue deteriorates in high and low temperature environments is solved, and the effect of significantly improving the thermal stability and impact resistance of the potting glue is achieved.
Patent Information
- Application Number
- CN202411006610.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-07-25
AI Technical Summary
The mechanical properties of existing potting glues are degraded in high and low temperature environments, making it difficult to meet the demand for high and low temperature performance of electronic devices.
The thermal stability and mechanical properties of the potting glue are enhanced by the modified boron carbide and silane modified magnesium oxide in the composite filler using component A, which includes a modified epoxy resin, a composite filler and a defoamer, and a curing agent and accelerator.
It significantly improves the high and low temperature resistance and impact resistance of potting adhesives, and enhances its stability and use value at different temperatures.
Smart Images

Figure BDA0004963170970000081 
Figure BDA0004963170970000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of potting adhesives, and in particular to a cold and heat shock resistant epoxy potting adhesive and a preparation method thereof. Background Art
[0002] Potting glue is used for bonding, sealing, potting and coating protection of electronic components. Potting glue is in liquid state before curing and has fluidity. The viscosity of the glue varies according to the material, performance and production process of the product. Potting glue can only realize its use value after it is completely cured. After curing, it can play the role of waterproof, moisture-proof, dust-proof, insulating, heat-conductive, confidential, anti-corrosion, temperature-resistant and shock-proof.
[0003] With the development of the electronic device industry, the requirements for the use environment of electronic devices are constantly increasing. However, when the potting compound is in an epoxy potting compound at too high or too low a temperature, the overall mechanical properties of the potting compound decrease, making it difficult to meet the performance requirements of the potting compound at high and low temperatures, so there is room for improvement. Summary of the invention
[0004] In order to solve the above problems, the present application provides a thermal shock resistant epoxy potting adhesive and a preparation method thereof.
[0005] The present application provides a thermal shock resistant epoxy potting adhesive and a preparation method thereof using the following technical solutions:
[0006] In the first aspect, the present application provides a thermal shock resistant epoxy potting adhesive, which adopts the following technical solution:
[0007] A thermal shock resistant epoxy potting adhesive, comprising component A and component B, wherein component A comprises a modified epoxy resin, a composite filler and a defoamer, and component B comprises a curing agent and an accelerator;
[0008] The composite filler comprises modified boron carbide and silane-modified magnesium oxide.
[0009] By adopting the above technical scheme, after adding composite fillers to component A, the performance of the epoxy resin system can be improved and promoted. The inorganic composite filler includes modified boron carbide and silane-modified magnesium oxide. The modified boron carbide has good high and low temperature resistance, as well as good thermal stability and mechanical properties. After being added as a filler, it can further improve the overall high and low temperature resistance of the potting compound, and at the same time can improve the impact resistance of the potting compound; after silane-modified magnesium oxide and modified boron nitride are compounded as thermal conductive materials, the compatibility of the inorganic filler in the system can be improved, and the occurrence of agglomeration of the inorganic filler in the system can be reduced, which has a significant improvement effect on the overall thermal stability and mechanical properties of the system.
[0010] Preferably, the modified boron nitride is prepared by the following method:
[0011] Boron nitride, dopamine hydrochloride, Tris buffer and ethanol are mixed, ultrasonically dispersed, stirred for reaction, filtered and solid products are collected, washed, and the obtained solid powder is dried to obtain dopamine-modified boron nitride; dopamine-modified boron nitride is mixed with polyvinyl pyrrolidone, added to N,N-dimethylformamide for ultrasonic dispersion to obtain a dispersion, silver nitrate is mixed with deionized water to obtain a silver nitrate solution, the silver nitrate solution is added to the dispersion, stirred for reaction, and after the reaction is completed, the solid product is collected by suction, washed and dried to obtain modified boron nitride.
[0012] By adopting the above technical solution, dopamine is used to modify boron nitride, and nanosilver particles are grown on the surface of the boron nitride sheet, which can bridge the boron nitride of the three-dimensional thermal conductive skeleton to improve the thermal stability and thermal conductivity of the composite material. At the same time, the overall mechanical strength of the system can be improved, and the potting compound can have good impact resistance.
[0013] Preferably, the mass ratio of the boron nitride, dopamine hydrochloride and silver nitrate is 1.99:(1-1.2):1.
[0014] By adopting the above technical solution, preferably the mass ratio of boron nitride, dopamine hydrochloride and silver nitrate is within the above range, which can effectively improve the overall performance of the inorganic filler.
[0015] Preferably, the silane-modified magnesium oxide comprises magnesium oxide and γ-aminopropyltriethoxysilane.
[0016] By adopting the above technical solution, amino groups and epoxy groups are introduced on the surface of magnesium oxide, which can improve the compatibility of magnesium oxide in epoxy resin, thereby improving the overall stability of the composite filler.
[0017] Preferably, the composite filler is prepared by the following method:
[0018] The modified boron nitride and silane-modified magnesium oxide are mixed and dispersed in anhydrous ethanol, and stirred for reaction. After the reaction is completed, the mixture is filtered, washed and dried to obtain a composite filler.
[0019] By adopting the above technical scheme, the dopamine-modified boron nitride and the silane coupling agent-modified magnesium oxide are compounded as inorganic fillers, which can improve the compatibility of the inorganic filler in the system and the dispersion of the inorganic filler in the system. At the same time, the compounding of boron nitride and magnesium oxide can further improve the overall mechanical properties of the system, so as to improve the overall impact resistance and thermal stability of the potting compound, and further improve the product quality of the prepared inorganic filler.
[0020] Preferably, the mass ratio between the modified boron nitride and the silane-modified magnesium oxide is 1:(0.9-1.1).
[0021] By adopting the above technical solution, the mass ratio between boron nitride and silane-modified magnesium oxide is preferably within the above range, which can further improve the overall comprehensive performance of the inorganic filler.
[0022] Preferably, the curing agent includes N-vinylimidazole, methyl acrylate and ethyl acrylate.
[0023] By adopting the above technical scheme, N-vinyl imidazole, methyl acrylate and ethyl acrylate are used as raw materials of the curing agent to prepare an imidazole curing agent, which can promote the ring-opening curing of the epoxy resin. The accelerator increases the flexible chain segments in the cured product, improves the tensile strength of the epoxy resin, and further enhances the overall impact resistance of the potting glue. At the same time, the accelerator has a high molecular weight polymer, which improves the cross-linking density of the system, and further improves the temperature resistance and thermal stability.
[0024] Preferably, the curing agent is prepared by the following method:
[0025] N-vinylimidazole, methyl acrylate and ethyl acrylate are mixed, N,N-dimethylformamide is added, stirred and heated to 75-85°C, azobisisobutyronitrile and dithiobenzoic acid are added after heating, stirred for reaction, and the product is precipitated after the reaction is completed, washed and dried to obtain a curing agent.
[0026] Preferably, the mass ratio of N-vinylimidazole, methyl propenyl ester and ethyl propenyl ester is (3-3.2):2:1.
[0027] By adopting the above technical solution, preferably the mass ratio of N-vinyl imidazole, methyl propylene and ethyl propylene is within the above range, which can further improve the overall comprehensive performance of the curing agent.
[0028] In the second aspect, the present application provides a method for preparing a thermal shock resistant epoxy potting adhesive, which adopts the following technical solution:
[0029] The steps include:
[0030] Preparation of component A: mixing epoxy resin and defoamer, stirring, adding composite filler, and continuing stirring to obtain component A; preparation of component B: mixing curing agent and accelerator, stirring to obtain component B.
[0031] Preparation of potting glue: Component A and component B are mixed and stirred to obtain an epoxy potting glue product.
[0032] In summary, the present application includes at least one of the following beneficial technical effects:
[0033] 1. In the present application, a composite filler is added to component A. The composite filler is composed of modified boron nitride and silane-modified magnesium oxide. The modified boron nitride has good high and low temperature resistance and good thermal stability. After compounding with silane-modified magnesium oxide, the compatibility of the composite filler in the system is significantly improved, and the composite filler can effectively improve the overall mechanical properties of the system, thereby greatly improving the comprehensive performance of the prepared potting compound;
[0034] 2. Boron nitride is modified by dopamine, and nano silver ions grow on the surface of boron nitride, bridging the three-dimensional thermal conductive skeleton boron nitride, thereby improving the stability of the composite material and the overall mechanical strength of the system. At the same time, it is compounded with silane-modified magnesium oxide to further improve the compatibility of the composite filler in the system, thereby further improving the overall thermal stability and impact resistance of the system;
[0035] 3. Using N-vinyl imidazole, methyl acrylate and ethyl acrylate as the raw materials of the accelerator, an imidazole accelerator is prepared. After being added to the components, it can promote the ring-opening curing of the epoxy resin. At the same time, it increases the content of the flexible segment of the cured product, increases the tensile strength of the epoxy resin, and thus improves the overall impact resistance of the potting compound. The overall cross-linking density of the system is increased, and the overall thermal stability of the potting compound system is further improved, so as to improve the product quality of the prepared potting compound. DETAILED DESCRIPTION
[0036] The present application discloses a thermal shock resistant epoxy potting adhesive and a preparation method thereof. The present application is further described in detail below in conjunction with the embodiments:
[0037] Raw material preparation: the defoaming agent is polydimethylsiloxane (CAS No.: 9016-00-6); the accelerator is Dow Corning OFS6040.
[0038] Example 1
[0039] Preparation of modified boron nitride:
[0040] 149.62 g of boron nitride, 75.19 g of dopamine hydrochloride (CAS No.: 62-31-7), 600 ml of Tris-HCl buffer (0.05 mol / L, 25° C.) and 120 ml of 95% ethanol solution were mixed, ultrasonically dispersed for 30 min, and stirred for reaction at 25° C. for 12 h. After the reaction, the dispersion was filtered and the solid product was collected. The product was washed and filtered with anhydrous ethanol. After the washing and filtering were repeated three times, the obtained solid powder was vacuum dried in an oven at 60° C. for 12 h to obtain dopamine-modified boron nitride. The dopamine-modified boron nitride prepared above was mixed with 40.23 g of polyvinylpyrrolidone. The obtained mixture was mixed with 1,2-dihydropyrrolidone (CAS No.: 9003-39-8), added to 600 ml of N,N-dimethylformamide (CAS No.: 68-12-2) and ultrasonically dispersed for 30 min to obtain a dispersion. 75.19 g of silver nitrate was mixed with 560 ml of deionized water, and stirred at a speed of 300 r / min for 20 min to obtain a silver nitrate solution. The silver nitrate solution was added to the dispersion, and stirred at 60 ° C for 2 h. After the reaction was completed, the temperature was lowered to 25 ° C, and the solid product was collected after filtration. It was washed three times with anhydrous ethanol, and the product was vacuum dried in an oven at 60 ° C for 12 h to obtain modified boron nitride.
[0041] Preparation of silane-modified magnesium oxide:
[0042] Mix 600 ml of anhydrous ethanol and 15 g of γ-aminopropyltriethoxysilane (CAS No.: 919-30-2), heat to 80°C, add 120 g of magnesium oxide, stir and react at a speed of 1300 r / min for 5 hours, cool to 25°C after the reaction, filter and wash with anhydrous ethanol three times, and dry the washed product in a vacuum oven at 80°C for 12 hours to obtain silane-modified magnesium oxide.
[0043] Preparation of composite fillings:
[0044] 105.26 g of modified boron nitride and 94.74 g of silane-modified magnesium oxide were mixed and dispersed in 500 ml of anhydrous ethanol. The mixture was heated to 90°C and stirred at 1200 rpm for 12 hours. After the reaction, the mixture was cooled to 25°C, filtered and washed three times with anhydrous ethanol, and then the product was vacuum dried at 80°C for 12 hours to obtain a composite filler.
[0045] Preparation of curing agent:
[0046] At a temperature of 25°C, 50.5g of N-vinyl imidazole (CAS No.: 1072-63-5), 33.33g of methyl acrylate (CAS No.: 96-33-3) and 16.17g of ethyl acrylate (CAS No.: 140-88-5) were mixed, 500mL of N,N-dimethylformamide was added, and nitrogen was purged for 10min. Then, under a nitrogen protective atmosphere, the mixture was stirred and heated to 75°C. After heating, 4.81g of azobisisobutyronitrile (CAS No.: 78-67-1) and 1.01g of dithiobenzoic acid (CAS No.: 121-68-6) were added. After stirring, the mixture was reacted for 3h. After the reaction was completed, the product was dispersed in ice ethanol to precipitate a white polymer. After centrifugation, the mixture was washed three times with deionized water, dried in an oven at 60°C for 12h, and crushed to obtain a curing agent.
[0047] Preparation of epoxy potting compound:
[0048] Preparation of component A: Dry 159 g of the composite filler in an oven at 80°C for 2 h, then cool to 25°C for standby use, mix 139 g of epoxy resin and 2 g of defoamer, put into a stirring kettle, stir at 700 rpm for 15 min, and maintain the vacuum degree at -0.09 MPa, add the dried composite filler, continue stirring for 25 min, and discharge to obtain component A;
[0049] Preparation of component B: Under an environment of 25° C., 49.45 g of the above-prepared curing agent and 0.55 g of the accelerator were mixed and dispersed in a stirring kettle, the vacuum degree was maintained at -0.090 MPa, and the mixture was stirred at a speed of 800 rpm for 15 min. Component B was obtained after discharging.
[0050] Preparation of potting glue: After mixing component A and component B, the temperature is raised to 100° C., stirred at a speed of 1800 rpm for 30 min, and cooled to room temperature to obtain an epoxy potting glue product.
[0051] Example 2
[0052] Preparation of modified boron nitride:
[0053] 142.48 g of boron nitride, 85.92 g of dopamine hydrochloride, 600 ml of Tris-HCl buffer (0.05 mol / L, 25° C.) and 120 ml of 95% ethanol solution were mixed, ultrasonically dispersed for 30 min, and stirred for reaction at 25° C. for 12 h. After the reaction was completed, the dispersion was filtered and the solid product was collected. Then, the solid product was washed and filtered with anhydrous ethanol. After the washing and filtering were repeated three times, the obtained solid powder was vacuum dried in an oven at 60° C. for 12 h to obtain dopamine-modified boron nitride. The dopamine-modified boron nitride prepared above was mixed with 40 .23g of polyvinyl pyrrolidone was mixed, added into 600ml of N,N-dimethylformamide and ultrasonically dispersed for 30min to obtain a dispersion, 71.6g of silver nitrate was mixed with 560ml of deionized water, stirred at 300r / min for 20min to obtain a silver nitrate solution, the silver nitrate solution was added to the dispersion, stirred at 60°C for 2h, after the reaction was completed, the temperature was lowered to 25°C, the solid product was collected after filtration, and washed three times with anhydrous ethanol, and the product was vacuum dried in an oven at 60°C for 12h to obtain modified boron nitride.
[0054] Preparation of silane-modified magnesium oxide:
[0055] Mix 600 ml of anhydrous ethanol and 15 g of γ-aminopropyltriethoxysilane, heat to 80°C, add 120 g of magnesium oxide, stir and react at a speed of 1300 r / min for 5 hours, cool to 25°C after the reaction, filter and wash with anhydrous ethanol three times, and dry the washed product in a vacuum oven at 80°C for 12 hours to obtain silane-modified magnesium oxide.
[0056] Preparation of composite fillings:
[0057] 95.24 g of modified boron nitride and 104.76 g of silane-modified magnesium oxide were mixed and dispersed in 500 ml of anhydrous ethanol. The mixture was heated to 90°C and stirred at 1200 rpm for 12 hours. After the reaction, the mixture was cooled to 25°C, filtered and washed three times with anhydrous ethanol, and then the product was vacuum dried at 80°C for 12 hours to obtain a composite filler.
[0058] Preparation of curing agent:
[0059] At a temperature of 25°C, 51.61g of N-vinyl imidazole, 32.26g of methyl acrylate and 16.13g of ethyl acrylate were mixed, 500mL of N,N-dimethylformamide was added, and nitrogen was purged for 10 minutes. Then, under a nitrogen protective atmosphere, the mixture was stirred and heated to 85°C. After heating, 4.81g of azobisisobutyronitrile and 1.01g of dithiobenzoic acid were added. The mixture was stirred and reacted for 3 hours. After the reaction was completed, the product was dispersed in ice ethanol to precipitate a white polymer. After centrifugation, the mixture was washed three times with deionized water, dried in an oven at 60°C for 12 hours, and crushed to obtain a curing agent.
[0060] Preparation of epoxy potting compound:
[0061] Preparation of component A: Dry 153.05 g of the composite filler in an oven at 80°C for 2 h, then cool to 25°C for standby use, mix 137.75 g of epoxy resin and 9.2 g of defoamer, put into a stirring kettle, stir at 700 rpm for 15 min, and maintain the vacuum degree at -0.09 MPa, add the dried composite filler, continue stirring for 25 min, and discharge to obtain component A;
[0062] Preparation of component B: Under an environment of 25° C., 46.43 g of the above-prepared curing agent and 3.57 g of the accelerator were mixed and dispersed in a stirring kettle, the vacuum degree was maintained at -0.090 MPa, and the mixture was stirred at a speed of 800 rpm for 15 min. Component B was obtained after discharging.
[0063] Preparation of potting glue: After mixing component A and component B, the temperature is raised to 100° C., stirred at a speed of 1800 rpm for 30 min, and cooled to room temperature to obtain an epoxy potting glue product.
[0064] Example 3
[0065] Preparation of modified boron nitride:
[0066] 145.97 g of boron nitride, 80.68 g of dopamine hydrochloride, 600 ml of Tris-HCl buffer (0.05 mol / L, 25° C.) and 120 ml of 95% ethanol solution were mixed, ultrasonically dispersed for 30 min, and stirred for reaction at 25° C. for 12 h. After the reaction was completed, the dispersion was filtered and the solid product was collected. Then, the solid product was washed and filtered with anhydrous ethanol. After the washing and filtering were repeated three times, the obtained solid powder was vacuum dried in an oven at 60° C. for 12 h to obtain dopamine-modified boron nitride. The dopamine-modified boron nitride prepared above was mixed with 40 .23g of polyvinyl pyrrolidone was mixed, added into 600ml of N,N-dimethylformamide and ultrasonically dispersed for 30min to obtain a dispersion, 73.35g of silver nitrate was mixed with 560ml of deionized water, stirred at 300r / min for 20min to obtain a silver nitrate solution, the silver nitrate solution was added to the dispersion, stirred at 60°C for 2h, after the reaction was completed, the temperature was lowered to 25°C, the solid product was collected after filtration, and washed three times with anhydrous ethanol, and the product was vacuum dried in an oven at 60°C for 12h to obtain modified boron nitride.
[0067] Preparation of silane-modified magnesium oxide:
[0068] Mix 600 ml of anhydrous ethanol and 15 g of γ-aminopropyltriethoxysilane, heat to 80°C, add 120 g of magnesium oxide, stir and react at a speed of 1300 r / min for 5 hours, cool to 25°C after the reaction, filter and wash with anhydrous ethanol three times, and dry the washed product in a vacuum oven at 80°C for 12 hours to obtain silane-modified magnesium oxide.
[0069] Preparation of composite fillings:
[0070] 100 g of modified boron nitride and 100 g of silane-modified magnesium oxide were mixed and dispersed in 500 ml of anhydrous ethanol. The temperature was raised to 90°C and stirred at 1200 rpm for 12 hours. After the reaction, the temperature was lowered to 25°C. After filtration, the mixture was washed three times with anhydrous ethanol. The product was then vacuum dried at 80°C for 12 hours to obtain a composite filler.
[0071] Preparation of curing agent:
[0072] At a temperature of 25°C, 50.82g of N-vinyl imidazole, 32.79g of methyl acrylate and 16.39g of ethyl acrylate were mixed, 500mL of N,N-dimethylformamide was added, and nitrogen was purged for 10 minutes. Then, under a nitrogen protective atmosphere, the mixture was stirred and heated to 80°C. After heating, 4.81g of azobisisobutyronitrile and 1.01g of dithiobenzoic acid were added. The mixture was stirred and reacted for 3 hours. After the reaction was completed, the product was dispersed in ice ethanol to precipitate a white polymer. After centrifugation, the mixture was washed three times with deionized water, dried in an oven at 60°C for 12 hours, and crushed to obtain a curing agent.
[0073] Preparation of epoxy potting compound:
[0074] Preparation of component A: Dry 122.45 g of the composite filler in an oven at 80°C for 2 h, then cool to 25°C for standby use, mix 172.35 g of epoxy resin and 5.2 g of defoamer, put into a stirring kettle, stir at 700 rpm for 15 min, and maintain the vacuum degree at -0.09 MPa, add the dried composite filler, continue stirring for 25 min, and discharge to obtain component A;
[0075] Preparation of component B: Under an environment of 25° C., 47.62 g of the above-prepared curing agent and 2.38 g of the accelerator were mixed and dispersed in a stirring kettle, the vacuum degree was maintained at -0.090 MPa, and the mixture was stirred at a speed of 800 rpm for 15 min. Component B was obtained after discharging.
[0076] Preparation of potting glue: After mixing component A and component B, the temperature is raised to 100° C., stirred at a speed of 1800 rpm for 30 min, and cooled to room temperature to obtain an epoxy potting glue product.
[0077] Example 4
[0078] Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing the composite filler, 117.65 g of modified boron nitride and 82.35 g of silane-modified magnesium oxide are weighed.
[0079] Example 5
[0080] Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing the composite filler, 86.96 g of modified boron nitride and 113.04 g of silane-modified magnesium oxide were weighed.
[0081] Example 6
[0082] Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, when preparing modified boron nitride, 157.52 g of boron nitride, 63.32 g of dopamine hydrochloride, and 79.16 g of silver nitrate are weighed.
[0083] Example 7
[0084] Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, when preparing the composite filler, 134.99 g of boron nitride, 95.67 g of dopamine hydrochloride, and 69.34 g of silver nitrate are weighed.
[0085] Example 8
[0086] Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, when preparing the curing agent, 47.37 g of N-vinyl imidazole, 35.09 g of methyl acrylate, and 17.54 g of ethyl propenyl acrylate were weighed.
[0087] Example 9
[0088] Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing the curing agent, 53.84 g of N-vinyl imidazole, 30.78 g of methyl acrylate, and 15.38 g of ethyl acrylate were weighed.
[0089] Example 10
[0090] Comparative Example 1
[0091] Comparative Example 1 is based on Example 3. The difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the composite filler replaces the modified boron nitride with ordinary boron nitride.
[0092] Comparative Example 2
[0093] Comparative Example 2 is based on Example 3. The difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the composite filler replaces the silane-modified magnesium oxide with ordinary magnesium oxide.
[0094] Comparative Example 3
[0095] Comparative Example 3 is based on Example 3. The difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, the composite filler has all silane-modified magnesium oxide replaced by an equal amount of modified boron nitride.
[0096] Performance testing
[0097] The epoxy potting adhesives of Examples 1-9 and Comparative Examples 1-3 were sampled and subjected to the following performance tests:
[0098] (1) Using GB / T 1732-2020 Determination of impact resistance of paint film and GB / T 1040-2006 Test of tensile properties of plastics as the test standards, the impact resistance of the samples was tested at -40℃, 25℃ and 180℃ respectively. Each sample was tested three times, and the average value was taken. The test results were filled in Table 1.
[0099] (2) Impact resistance test
[0100] Taking GB / T 1040-2006 Test of Tensile Properties of Plastics as the test standard, the tensile properties of the samples were tested at -40℃, 25℃ and 180℃ respectively. Each sample was tested three times, and the average value was taken and the test results were filled in Table 1.
[0101] (3) Insulation performance test
[0102] According to GB T 1410-2006 Solid Insulating Material Volume Resistivity and Surface Resistivity Test Method Standard, the insulation performance of the samples was tested. Each sample was tested three times, and the average value was taken. The test results were filled in Table 1.
[0103]
[0104]
[0105] Performance data analysis From Table 1, it can be seen that in Examples 1-3, the impact resistance at -40°C, 25°C and 180°C is 39.0 J / cm 2 The tensile strengths at -40°C, 25°C and 180°C are all above 13.5 MPa, indicating that the present invention has good high and low temperature resistance and good impact resistance. The insulation performance of Examples 1-3 is all above 1.12×10 15 Ω·cm and above, indicating that the epoxy potting adhesive prepared in the present application has good insulation performance.
[0106] In the preparation of composite fillers, when the content of silane-modified magnesium oxide is too high, it is difficult for the silane-modified magnesium oxide to settle evenly on the surface of the modified boron nitride. The two reduce the uniformity of the distribution of the silane-modified magnesium oxide in the system and cause agglomeration, thereby affecting the overall stability of the composite filler and further affecting the product quality of the epoxy potting compound; when the proportion of silane-modified magnesium oxide is too small, the compatibility between the composite filler and the epoxy resin system is affected, the interface gap between the composite filler and the epoxy resin increases, and the overall thermal stability and mechanical properties of the system are affected. Therefore, the performance of Examples 4 and 5 are all reduced.
[0107] When preparing modified boron nitride, when the content of boron nitride is too much, the modification effect of dopamine on the surface of boron nitride is reduced, and at the same time, the distribution uniformity of nano-silver ions on the surface of boron nitride is affected, the performance improvement effect of boron nitride is reduced, and the overall performance of the prepared epoxy potting glue product is affected; when the content of boron nitride is too little, the thickness of the dopamine coating formed on the surface of boron nitride will be too thick, and the distribution uniformity of nano-silver ions on the surface of boron nitride will be reduced, and some nano-silver ions will be free in the system and agglomerated, thereby affecting the dispersion effect of the composite filler in the system, and further affecting the product quality of the epoxy potting glue. Therefore, the various performances of Example 6 and Example 7 are reduced.
[0108] When preparing the curing agent, when the content of N-vinylimidazole is too little, the nitrogen atom content decreases, the reaction activity of the curing agent decreases, the ring-opening promotion effect on the epoxy resin is weakened, and the binding effect between too little N-vinylimidazole and methyl acrylate and ethyl acrylate decreases, which affects the product quality of the curing agent; when the content of N-vinylimidazole is too much, the content of acrylate decreases, and the flexible segment in the curing agent decreases, thereby reducing the tensile strength of the cured epoxy potting glue and affecting the impact resistance of the system. Therefore, the corresponding performances of Example 8 and Example 9 are reduced.
[0109] In Comparative Example 1, the modified boron nitride is replaced with ordinary boron nitride. The interface compatibility between ordinary boron nitride and epoxy resin decreases, which introduces a larger interface thermal resistance at the interface between the composite filler and the epoxy resin, affecting the overall thermal stability of the system, and reducing the dispersion effect of boron nitride in the system, thereby reducing the stability of the prepared epoxy potting compound. Therefore, the various performances of Comparative Example 1 are reduced.
[0110] In Comparative Example 2, the silane-modified magnesium oxide was replaced with ordinary magnesium oxide, which affected the compatibility between magnesium oxide and epoxy resin, caused the composite filler to agglomerate in the system, and affected the overall stability of the system, so the various properties in Comparative Example 2 were reduced.
[0111] In Comparative Example 3, all the silane-modified magnesium oxide in the composite filler is replaced by an equal amount of modified boron nitride. A single filler is difficult to effectively construct a thermal conductive network, which reduces the overall thermal stability of the epoxy potting system and makes it difficult to improve the mechanical properties. Therefore, the overall performance of the system in Comparative Example 3 is reduced.
[0112] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A thermal shock resistant epoxy potting adhesive, characterized by: The invention comprises component A and component B, wherein component A comprises modified epoxy resin, composite filler and defoamer, and component B comprises curing agent and accelerator; The composite filler comprises modified boron nitride and silane-modified magnesium oxide; The modified boron nitride is prepared by the following method: Boron nitride, dopamine hydrochloride, Tris buffer and ethanol are mixed, ultrasonically dispersed, stirred for reaction, filtered and solid products are collected, washed, and the obtained solid powder is dried to obtain dopamine-modified boron nitride; dopamine-modified boron nitride is mixed with polyvinyl pyrrolidone, added to N,N-dimethylformamide for ultrasonic dispersion to obtain a dispersion, silver nitrate is mixed with deionized water to obtain a silver nitrate solution, the silver nitrate solution is added to the dispersion, stirred for reaction, filtered and solid products are collected, washed and dried to obtain modified boron nitride; The silane-modified magnesium oxide comprises magnesium oxide and γ-aminopropyltriethoxysilane; The composite filler is prepared by the following method: The modified boron nitride and silane-modified magnesium oxide are mixed and dispersed in anhydrous ethanol, stirred for reaction, filtered, washed and dried to obtain a composite filler; The curing agent includes N-vinyl imidazole, methyl acrylate and ethyl acrylate; The curing agent is prepared by the following method: N-vinylimidazole, methyl acrylate and ethyl acrylate are mixed, N,N-dimethylformamide is added, stirred and heated to 75-85°C, azobisisobutyronitrile and dithiobenzoic acid are added after heating, stirred for reaction, and the product is precipitated after the reaction is completed, washed and dried to obtain a curing agent.
2. The hot and cold shock resistant epoxy potting adhesive according to claim 1, characterized in that: The mass ratio of the boron nitride, dopamine hydrochloride and silver nitrate is 1.99:(1-1.2):
1.
3. The hot and cold shock resistant epoxy potting adhesive according to claim 1, characterized in that: The mass ratio between the modified boron nitride and the silane-modified magnesium oxide is 1:(0.9-1.1).
4. The hot and cold shock resistant epoxy potting adhesive according to claim 1, characterized in that: The mass ratio of N-vinyl imidazole, methyl propenyl ester and ethyl propenyl ester is (3-3.2):2:
1.
5. A method for preparing the cold and heat shock resistant epoxy potting adhesive according to claim 1, characterized in that: The steps include: Preparation of component A: Mixing the modified epoxy resin and the defoamer, stirring, adding the composite filler, and continuing to stir to obtain component A; Prepare component B: mix the curing agent and the accelerator and stir to obtain component B; Preparation of potting glue: Component A and component B are mixed and stirred to obtain an epoxy potting glue product.
Citation Information
Patent Citations
Epoxy filling adhesive with high thermal conductivity and preparation method of epoxy filling adhesive
CN110055020A
Modified boron nitride-magnesium oxide / epoxy resin heat-conducting composite material and preparation method thereof
CN115785622A